A critical overview of the current myofascial pain literature – September 2016. Issue 4 (October 2016) - Dommerholt, Jan; Finnegan, Michelle; Hooks, Todd; Grieve, Rob
Summary: This edition of the overview of the current myofascial pain literature includes 24 studies, case reports and systematic and narrative reviews. Surprisingly, five of the 24 papers were difficult to read and interpret mostly because of a poor mastery of the English language. It is somewhat surprising that journal editors and reviewers would accept papers that are needlessly difficult to read and not direct the authors to language services or others who could improve the quality of the writings. Of course, it is exciting that researchers and clinicians from all over the world continue to focus on myofascial pain and attempt to shed new light on the complexity of the problem to improve the clinical decision-making process and eventually clinical approaches and outcomes. There were no new papers on manual therapies, but many focused on dry needling.